Remote Ischemic Conditioning on Recipients of Deceased Renal Transplants Does Not Improve Early Graft Function: A Multicenter Randomized, Controlled Clinical Trial. Issue 4 (9th November 2016) - Krogstrup, N. V.; Oltean, M.; Nieuwenhuijs‐Moeke, G. J.; Dor, F. J. M. F.; Møldrup, U.; Krag, S. P.; Bibby, B. M.; Birn, H.; Jespersen, B.
Abstract : Delayed graft function is a frequent complication following deceased donor renal transplantation, and is closely related to ischemia–reperfusion injury. Experimental and clinical studies have shown protection by remote ischemic conditioning (RIC). We hypothesized that recipient RIC before kidney graft reperfusion reduces the time to graft recovery. This multicenter, blinded, randomized, controlled clinical trial included 225 adult recipients of renal transplants from deceased donors at four transplantation centers in Denmark, Sweden, and the Netherlands. Participants were randomized 1:1 to RIC or sham‐RIC. RIC consisted of 4 × 5‐min thigh occlusion by an inflatable tourniquet each followed by 5‐min deflation, performed during surgery prior to graft reperfusion. The tourniquet remained deflated for sham‐RIC. The primary endpoint was the estimated time to a 50% decrease in baseline plasma creatinine (tCr50) calculated from plasma creatinine measurements 30 days posttransplant or 30 days after the last, posttransplant dialysis. No significant differences were observed between RIC and sham‐RIC‐treated patients in the primary outcome median tCr50 (122 h [95% confidence interval [CI] 98–151] vs. 112 h [95% CI 91–139], p = 0.58), or the number of patients receiving dialysis in the first posttransplant week (33% vs. 35%, p = 0.71). Recipient RIC does not reduce the time to graft recovery in kidney transplantation from deceased donors. ClinicalTrials.gov: NCT01395719. Abstract : In this randomized, controlled clinical trial, the authors apply remote ischemic conditioning on recipients of deceased donor renal transplants and find it has no effect on early kidney graft function.